Sovremennye tehnologii formirovanija dvigatel'nyh umenij i navykov v processe obuchenija slozhnokoordinacionnym sportivnym uprazhnenijam - Boloban, V. (Science in Olympic Sport, 2017)
The article shows the relevance of scientific research into the problem of teaching motor actions on the basis of the progress of increasing difficulty of exercises in complex coordination sports. The structural composition of sports exercises is studied, the role and the influence of the multidisciplinary content of motor actions on the optimization of teaching sports exercises are shown. The multidisciplinary components and peculiarities of development of motor skills and exercise abilities to be mastered are based on the understanding, consideration and use of mechanisms controlling irradiation, concentration, and stabilization of excitation and inhibition processes in the central nervous system. Modern technologies for teaching motoractions are implemented on the basis of biomechanical, psychological, and pedagogical parameters and individual indicators of athletic preparedness of participants. Algorithms for using biological feedback as a modern approach to self-assessment and self-regulation are examined, as well as a technology for methodological and practical assistance to a trainer, a scientist, and an athlete in the process of teaching a sports exercise.